The role of family support in the well-being of older people: Evidence from Malaysia and Viet Nam - Yana Rodgers; Joseph E. Zveglich; Khadija Ali; Hanna Xue (Asian Development Bank (ADB), 2024)
Demographics in Malaysia and Viet Nam are evolving rapidly, potentially disrupting traditional family support to older people. We estimate a set of Poisson random effects models with panel data from the Malaysia Ageing and Retirement Survey and the Viet Nam Aging Survey to analyze how living arrangements, marital status, and support from children influence the mental and physical health of older people. In Malaysia, having living children plays an important protective role for both mental and physical health, while living with a son appears to have a protective effect for physical health. Results are similar for Viet Nam, except older women, who are at greater risk of mental and physical health problems, appear to enjoy a greater protective effect for their mental health from a child living nearby than do men. Our analysis underscores the importance of social safety nets for the health of senior citizens living alone.
Keywords: I14; J16; O53; 330; mental health; well-being; physical health; depression; gender; women; aging